Psychometric properties of the Czech moral injury symptom scale - Vlckova, Karolina; Janouskova, Miroslava; Bankovska-Motlova, Lucie (Scientific reports, 2025)
Moral injury is defined as a deep sense of transgression, including feelings of shame, grief, meaninglessness, and remorse from having violated core moral beliefs. This study aimed to adapt the Moral Injury Symptom Scale-Healthcare Professionals (MISS-HP) for measure this concept in the Czech Republic and explore its psychometric properties. Sample of healthcare providers (N = 694) completed the MISS-HP questionnaires, the Shirom Melamed Burnout Measure (SMBM) and the Professional Quality of Life scale (PROQoL). Cronbach´s alpha of MISS-HP was found to be 0.62; exploratory factor analysis returned 4 factors. Correlations with SMBM and PROQoL were moderate (from 0.31-0.46), which confirmed the construct validity of MISS-HP. ROC curve analysis identified the optimal cut-off score at 42 points with 75% sensitivity and 69% specificity. Female gender, younger age and atheism were related to higher symptoms of moral injury. Czech MISS-HP was found to be a valid and reliable measure of moral injury.
Keywords: dospělí; Health Personnel; MISS-HP; průzkumy a dotazníky; Female; Psychometrics; psychometrie; Covid-19; Quality of Life; Adult; ženské pohlaví; zdravotnický personál; Surveys and Questionnaires; Reproducibility of Results; kvalita života; lidé; reprodukovatelnost výsledků; Male; Healthcare professionals; Czech Republic; profesionální vyhoření; Burnout, Professional; mravy; Česká republika; Morals; lidé středního věku; mužské pohlaví; Moral injury; Middle Aged; Humans